Quality Management in Madrasas Based on IASP 2020 - Heri Gunawan; Mohamad Jaenudin; Sarbini Sarbini; Fuad Hilmi (Khazanah Pendidikan Islam, 2023)
Quality is a very important thing to be implemented in educational institutions, including Islamic educational institutions. One of the efforts to maintain the quality of education is to implement a management system based on the IASP 2020. In Islamic education institutions based on Islamic boarding schools such as MI, MTs and MA, the implementation of IASP 2020 has not been maximized, therefore it is necessary to provide assistance in implementing it. This is the background of this dedication. The purpose of service is to provide a deep understanding to MI educators and education staff. MTs and MA which are under the auspices of YPI Al-Qonaah Cikajang, Garut Regency. The method used is by using the workshop method where participants are actively involved in filling out the IASP 2020 and conducting follow-up programs. The service activity was attended by educators and education staff at YPI Al-Qonaah Cikajang Garut, the activity went smoothly and asked for follow-up on these activities.